Socio-economic status and antisocial behavior of children and teenagers. - S. A. Schudro (Medičnì Perspektivi)
National Institute for Health and Clinical Excellence (NICE) and a number of conducted aim analyses, confirmed the presence of intercommunications between socio-economic status of children and teenagers and their antisocial behavior and distinguished the role of such factors, as their psychological features, age and sex. The clinical and psychological inspection of teenagers enabled to distinguishin them such types of personality forming as: aggressive, labial states, instable, with "absence of brake", sexually-fixed, hysteroid, apathetical, schizoid, paranoidal. Processes of socialization, absence or presence of paternal attention to education, capacity for co-operation between parents and teenagers, depression in a mother or father, genetic and phenotype (external) factors cause antisocial behavior of teenagers. It is shown, that genetic factors that affect antisocial behavior of teenagers were more expressive in rich families, while phenotype (external) – in poor families. A review of undertaken studies showed, that there is the necessity of deep research of interaction of social and biological factors for understanding of the role of socio-economic factors in forming of antisocial behavior of children and teenagers.